2015
DOI: 10.3758/s13428-015-0632-x
|View full text |Cite
|
Sign up to set email alerts
|

Online versus offline: The Web as a medium for response time data collection

Abstract: The Internet provides a convenient environment for data collection in psychology. Modern Web programming languages, such as JavaScript or Flash (ActionScript), facilitate complex experiments without the necessity of experimenter presence. Yet there is always a question of how much noise is added due to the differences between the setups used by participants and whether it is compensated for by increased ecological validity and larger sample sizes. This is especially a problem for experiments that measure respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 23 publications
4
50
0
1
Order By: Relevance
“…Additionally, it is worth noting that RTs during the EST for participants in the neutral condition did not differ as a function of location. This finding is at odds with several studies showing significantly slower overall RTs remotely (Chetverikov & Upravitelev, ; Reimers & Stewart, ), but consistent with a recent study showing no difference in overall RTs between the laboratory and remotely (Miller et al ., ). The mixed findings in the literature makes it difficult to determine why our findings were not internally consistent, although in the context of the current study the emotion provocation may have played a role in the slower overall RTs found remotely.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Additionally, it is worth noting that RTs during the EST for participants in the neutral condition did not differ as a function of location. This finding is at odds with several studies showing significantly slower overall RTs remotely (Chetverikov & Upravitelev, ; Reimers & Stewart, ), but consistent with a recent study showing no difference in overall RTs between the laboratory and remotely (Miller et al ., ). The mixed findings in the literature makes it difficult to determine why our findings were not internally consistent, although in the context of the current study the emotion provocation may have played a role in the slower overall RTs found remotely.…”
Section: Discussionsupporting
confidence: 75%
“…All study procedures were approved by the Institutional Review Board of the University of Texas at Austin. Based on simulation experiments conducted by Chetverikov and Upravitelev () we determined that approximately 80 participants per group would provide sufficient power to detect a small (10 ms) difference in RTs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although methodological challenges will need to be addressed in future optimizations, an increasing number of studies indicate that the timing characteristics of browser-based experiments are acceptable enough to warrant the replication of default laboratory experiments (Barnhoorn, Haasnoot, Bocanegra, & van Steenbergen, 2015; Chetverikov & Upravitelev, 2015; de Leeuw, 2015; de Leeuw & Motz, 2015; Garaizar, Vadillo, & López-de-Ipiña, 2014; Keller, Gunasekharan, Mayo, & Corley, 2009; Neath, Earle, Hallett, & Surprenant, 2011; Reimers & Stewart, 2015; Schubert, Murteira, Collins, & Lopes, 2013; Slote & Strand, 2015; von Bastian, Locher, & Ruflin, 2013). In particular, the introduction of HTML5 presentation techniques has enabled frame-wise stimulus presentation for browser-based experiments, a method we have included in the QRTEngine (Barnhoorn et al., 2015), which allows millisecond accuracy to be approached (Garaizar et al., 2014).…”
mentioning
confidence: 99%
“…The psychological society tends not to trust the precision of tests administered online because of the potential confounding factors such as the technical properties of the personal computers or monitors of the respondents. However, the quantitative estimation of the noise added due to the differences in setup shows that at least for some type of tasks web-based experiments can be an acceptable source of data [26]. Thus, the next logical step for the computerized cognitive tests is to spread across the internet the same way it has happened to the questionnaires.…”
Section: Analysis Of Platforms For Psychological Researchmentioning
confidence: 99%